2021
DOI: 10.1186/s40337-021-00403-x
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorder Examination Questionnaire (EDE-Q-13): expanding on the short form

Abstract: Objective The Eating Disorders Examination–Questionnaire (EDE-Q) is widely used but time-consuming to complete. In recent years, the advantages and disadvantages of several brief versions have therefore been investigated. A seven-item scale (EDE-Q-7) has excellent psychometric properties but excludes items on bingeing and purging. This study aimed to evaluate a thirteen-item scale (EDE-Q-13) including items on bingeing and purging. Method Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 30 publications
1
34
0
1
Order By: Relevance
“…EDE-Q-13 consists of 13 items and 5 subscales, namely Eating Restraint (ER), Shape and Weight Over-Evaluation (SWO), Body Dissatisfaction (BD), Bingeing, and Purging [ 25 ]. Its validity study was conducted by Lev-Ari et al [ 25 ], and the scale showed a strong positive correlation with the original EDE-Q.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…EDE-Q-13 consists of 13 items and 5 subscales, namely Eating Restraint (ER), Shape and Weight Over-Evaluation (SWO), Body Dissatisfaction (BD), Bingeing, and Purging [ 25 ]. Its validity study was conducted by Lev-Ari et al [ 25 ], and the scale showed a strong positive correlation with the original EDE-Q.…”
Section: Methodsmentioning
confidence: 99%
“…Among the short versions of EDE-Q, the 3-factor EDE-Q-7 (Dietary Restraint, Shape and Weight Over-Evaluation, Body Dissatisfaction) yielded excellent psychometric properties; however, it might yield incomplete data because it does not include items about "binge eating" and "purging", which are important in evaluating the symptoms of eating disorders [ 20 ]. Therefore, the 13-item 5-factor short-form of EDE-Q-13 was developed by Lev-Ari et al [ 25 ]. In addition to the 7 items of the original EDE-Q-7, this scale includes 6 more items, all of which are related to binge eating and purging.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations